2017
DOI: 10.1007/s00705-017-3318-0
|View full text |Cite
|
Sign up to set email alerts
|

An update on the rabbit hemorrhagic disease virus (RHDV) strains circulating in Portugal in the 1990s: earliest detection of G3-G5 and G6

Abstract: Rabbit hemorrhagic disease virus (RHDV) causes devastating effects on European rabbit (Oryctolagus cuniculus) populations in the Iberian Peninsula. According to the information available, only genogroup 1 strains were circulating in Iberian wild rabbits until 2011; the antigenic variant G6 has been sporadically detected in rabbitries since 2007. Here, we show for the first time that G3-G5 strains were already present in mainland Portugal in 1998 and that G6 has been circulating since at least 1999. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…These observations [108] have been confirmed in studies of 7 GI.1-RHDV viruses [65], but with different HA ability, (3 GI.1-RHDV HA+ viruses, 2 HA− viruses, 2 HA+/− viruses) and 11 GI.1a-RHDVa HA+ viruses analysed on the basis of their whole genome, obtained from Poland between 1988 and 2015, which distinguished four phylogenogroups among the 18 viruses studied. They showed that the less pathogenic GI.1-RHDV viruses, relative to GI.1a-RHDVa viruses, represent three phylogenogroups, while the fourth phylogenogroup is formed by GI.1a-RHDVa viruses, which would confirm the data that GI.1a-RHDVa viruses form a separate fourth phylogenogroup [1,106,113] GI.1a-RHDVa viruses have a different structure and pathogenicity from GI.1a-RHDVa viruses, which determines their immunogenicity [8,9,16,53,96,100,107]. Also, the analysis [60] based on the evaluation of the nucleotide sequences encoding the VP60 protein concerning the occurrence of phylogenogroups within 43 GI.1-RHDV viruses with different HA abilities (42 HA+ viruses, 1 HA+/− virus) and 36 GI.1a-RHDVa viruses, also with different HA abilities (15 HA+ viruses, 3 HA− viruses, 18 HA viruses unspecified), and 2 RCV viruses, now GI.3, GI.4-RCV, from different countries in Europe, Asia, America and Australia from 1985 to 2010 showed that these 81 analysed viruses form four phylogenogroups, which do not include the 2 analysed RCV viruses (now GI.3, GI.4-RCV).…”
Section: Phylogenogroups Of Lagovirus Europaeus Gi-rhdv Viruses and T...mentioning
confidence: 66%
“…These observations [108] have been confirmed in studies of 7 GI.1-RHDV viruses [65], but with different HA ability, (3 GI.1-RHDV HA+ viruses, 2 HA− viruses, 2 HA+/− viruses) and 11 GI.1a-RHDVa HA+ viruses analysed on the basis of their whole genome, obtained from Poland between 1988 and 2015, which distinguished four phylogenogroups among the 18 viruses studied. They showed that the less pathogenic GI.1-RHDV viruses, relative to GI.1a-RHDVa viruses, represent three phylogenogroups, while the fourth phylogenogroup is formed by GI.1a-RHDVa viruses, which would confirm the data that GI.1a-RHDVa viruses form a separate fourth phylogenogroup [1,106,113] GI.1a-RHDVa viruses have a different structure and pathogenicity from GI.1a-RHDVa viruses, which determines their immunogenicity [8,9,16,53,96,100,107]. Also, the analysis [60] based on the evaluation of the nucleotide sequences encoding the VP60 protein concerning the occurrence of phylogenogroups within 43 GI.1-RHDV viruses with different HA abilities (42 HA+ viruses, 1 HA+/− virus) and 36 GI.1a-RHDVa viruses, also with different HA abilities (15 HA+ viruses, 3 HA− viruses, 18 HA viruses unspecified), and 2 RCV viruses, now GI.3, GI.4-RCV, from different countries in Europe, Asia, America and Australia from 1985 to 2010 showed that these 81 analysed viruses form four phylogenogroups, which do not include the 2 analysed RCV viruses (now GI.3, GI.4-RCV).…”
Section: Phylogenogroups Of Lagovirus Europaeus Gi-rhdv Viruses and T...mentioning
confidence: 66%
“…The 00-21 strain belongs to the GI.1d variant group according to the proposal for a unified classification system for lagoviruses [9]. Complete or almost complete GI.1d genome sequences (without complete UTR sequences) from Bahrain in 2001 and from European countries collected until 2004 have been already obtained [11,18,19], but not from France where this variant has circulated since 1990 [10,12]. The present study characterised the complete genome sequence of a GI.1d strain collected in France in 2000.…”
Section: Discussionmentioning
confidence: 99%
“…And in a short period, about 140 million rabbits died of the disease, and the spread area was as high as 50,000 square kilometers, causing enormous damage to the country’s economy. Subsequently, the virus was also discovered in Italy in 1986 [ 3 ] and spread to other European countries, such as Spain and Portugal in the following year, causing serious damage to the local ecological environment [ 4 , 5 ]. In 1988, the first recorded outbreak in Mexico City, the Mexican government took strict clearance measures and became the only country to eradicate RHD.…”
Section: Introductionmentioning
confidence: 99%